The Funds National Archive of Uzbekistan as A Historical Source on the History of Justice Problem sin Turkestan ASSR - D.B. Toshtemirov (Zien Journals, 2022)
This article provides an overview of the fund R-38 of the People's Commissariat of Justice of the Turkestan ASSR, which is stored in the National Archives of Uzbekistan. In particular, the content, types and safety of archival documents stored in the fund are analyzed
Keywords: Archive; documents; Turkestan ASSR; National Archive of Uzbekistan